WAYS TO ENHANCE THE PSYCHOLOGICAL AND PEDAGOGICAL COMPETENCE OF OFFICERS IN THE MILITARY UNITS OF UKRAINEʹS DEFENCE FORCES - Savchuk, Oleksandr; Pasichnyk, Volodymyr; Tovma, Mykola (Honor and Law, 2025)
The article examines ways of improving the psychological and pedagogical competencies of officers of the Defence Forces of Ukraine under the conditions of repelling large-scale armed aggression. Based on a theoretical analysis of scientific literature and an empirical study, fifteen critically important psychological and pedagogical competencies have been identified, and ten practical approaches to their improvement have been proposed. The application of the study's results is suggested for updating officer training programs and organizing their professional development in the course of service and combat activities.